Mendengarkan Aktif sebagai Upaya Pengembangan Soft Skill Komunikasi Antar Pasangan di Kalangan Mahasiswa - Muhammad Fauzan Azhima; Ramlan Aryan Permana (shofanah Media Berkah, 2026)
Active listening is a crucial interpersonal skill that plays a significant role in shaping an individual's communication skills. Among college students, this skill is considered a soft skill needed to support academic and social interactions, particularly in communication between pairs of students interacting with each other. This study aims to examine the role of active listening in developing soft communication skills between pairs of students through a case study approach. The method used is a case study by observing student communication patterns during discussions and pair interactions in class. The results of the study indicate that the application of active listening can increase mutual understanding, empathy, and communication effectiveness. Thus, active listening plays an important role in developing students' soft communication skills.